HANDICAPS ENCOUNTERED IN LEARNING VOCABULARY BY THE EIGHTH YEAR STUDENTS OF SLTP NEGERI 3 SESEAN - Selvi Panggua (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Indonesia Toraja, 2011)
SELVI PANGGUA, 2009. HANDICAPS ENCOUNTERED IN LEARNING VOCABULARY BY THE EIGHTH YEAR STUDENTS OF SLTP NEGERI 3 SESEAN. A Journal. (vii + 37 Pages; 14 tables) The problem of this research is what are the handicaps encountered in learning vocabulary by the eighth year students of SLTP NEGERI 3 SESEAN The objective of the research is to find out the handicaps encountered in learning vocabulary by the eighth year students of SLTP NEGERI 3 SESEAN. The population of this research was the eighth students SLTP NEGERI 3 SESEAN academic year 2008/2009.it consists of 60 students and the writer took only 30 students randomly as sample from the presence list. In doing this research, the writer employed descriptive method. she collected data by using only one kind of instrument namely questionnaire, it aimed at finding out the handicaps encountered in learning vocabulary by the eighth year students of SLTP NEGERI 3 SESEAN. Based on the result of the data analysis tell us that the eighth year students of SLTP NEGERI 3 SESEAN: The vocabulary material given by their English teacher is difficult The students had limited knowledge about the English. The school library did not prepare enough number of books at English vocabulary. The students rarely memorized vocabulary. Most of students did not have dictionary. The English teacher of SLTP Negeri 3 Sesean still neglects the teaching of English vocabulary to the students especially in giving explain about the vocabulary. The students have low interest in learning vocabulary. Based on the explanation above, the writer concludes that the eighth year students of SLTP Negeri 3 Sesean still encountered handicaps in learning vocabulary.